Recombinant human erythropoietin accelerated the proliferation of non‐small cell lung cancer cell lines and reduced the expression of VEGF, HIF‐1α, and PD‐L1 under a simulated hypoxic environment in vitro - Yajing Zhang; Yangchun Feng; Xiaojie Sun (Chronic Diseases and Translational Medicine, 2022)
Abstract Background As erythropoietin (EPO) has been used to treat anemia in cancer patients, negative controversy has continued. Unfortunately, its effects on non‐small‐cell lung carcinoma (NSCLC) cell lines are uncertain and the phenomenon of inducing immune escape of tumor cells remains to be explored. This study aimed to provide an important basis for the application of exogenous EPO in the treatment of tumor‐associated anemia. Methods Cells were cultured in 1% O2, 5% CO2, and 94% N2 to simulate a hypoxic environment of the tumor. A549 cell line (lower expression EPOR) and NCI‐H838 cell line (higher expression EPOR) were treated with 2 and 8 U/ml recombinant human EPO (rhEPO). CCK‐8 method was used to determine the logarithmic growth phase of the cells and to detect cell proliferation. The expression levels of VEGF, HIF‐1α, and PD‐L1 were determined by western blot. One‐way ANOVA was used for statistical analysis between groups, with p < 0.05 indicating a significant difference. Results Hypoxia itself could decrease the survival rate of NSCLC cells. Under the hypoxic condition, rhEPO induced tumor cells proliferation, especially in the NCI‐H838 cell line, where 2 U/ml rhEPO increased the total number of surviving cells (Hypoxia + rhEPO 2 U/ml vs. Hypoxia, p < 0.05). Western blot analysis showed that hypoxia upregulated the expression of VEGF, HIF‐1α, and PD‐L1 in NSCLC cell lines (Normoxia vs. Hypoxia, p < 0.05), but may not be dependent on the expression levels of EPOR. RhEPO decreased the expression levels of VEGF and HIF‐1α. In the A549 cell line, it depended on the concentration of rhEPO and was particularly obvious in HIF‐1α (Hypoxia vs. Hypoxia + rhEPO 2 U/ml vs. Hypoxia + rhEPO 8 U/ml, p < 0.05). A low concentration of rhEPO may not reduce VEGF expression. In the NCI‐H838 cell line, the effect of rhEPO on VEGF was more obvious, but it may be independent of rhEPO concentrations. The downregulation of PD‐L1 expression by rhEPO was only presented in the A549 cell line and required higher rhEPO concentrations (Hypoxia + rhEPO 8 U/ml vs. Hypoxia&Hypoxia + rhEPO 2 U/ml, p < 0.05). Conclusion The effect of prolonged high concentrations of rhEPO under hypoxic conditions resulted in accelerated cells proliferation of non‐small‐cell lung cancer and was independent of EPOR expression levels on the cell lines surface. Hypoxia resulted in increased expression of VEGF, HIF‐1α, and PD‐L1 on the NSCLC cell lines. Under normoxic conditions, rhEPO did not affect the expression of VEGF, HIF‐1α, and PD‐L1; but under hypoxic conditions, the application of rhEPO reduced the expression of VEGF, HIF‐1α, and PD‐L1, producing an impact on the biological behavior of tumor cells.